Evaluation of Effect of Egg Replacer in Cake Making - Nova Sarifah Dewi; Elisa Julianti; Zulkifli Lubis (Universitas Sumatera Utara, 2015)
The research was aimed to evaluate the functional characteristics and sensory quality of cakes made of soy protein isolate, whey protein isolate, corn starch, guar gum, and whole egg powder. The research had been performed using a non factorial completely randomized design with 7 levels and 3 repetitions. The egg replacer composition were E1 = whey protein isolate, corn starch, and guar gum (12,0 g : 5,2 g : 1,0 g) ; E2 = soy protein isolate, corn starch, and guar gum (12,0 g : 5,2 g : 1,0 g ); and E3 = whole egg powder (18,2 g). Parameters analyzed were water content, ash content, protein content, fat content, crude fiber content, carbohydrate content, specific volume, browning index and organoleptic (color, flavor, aroma, texture). The results showed that the cake with different egg replacer composition had different physicochemical and sensory characteristics. The cake made by using egg replacer from whey protein isolate, corn starch, and xanthan gum (12,0 g : 5,2 g : 1,0 g ) had the good physicochemical quality and accepted by panelists . Keywords: Egg replacer, cake, whole egg powder